The Discrepancy between HbA1c and CGM-Derived GMI in Diabetes Management: A Retrospective Cohort Study - A. Manov; Y. Badi; A. Donepudi; N. Holt; M. Sharaf; R. Rivera; A. Daliwal; R. Haddadin; I. Quadir; K. Mefferd (Medical Research and Its Applications Vol. 4, 2024)
We performed a retrospective observational cohort study between 2020-2023 in 26 patients with type-1 and type-2 Diabetes Mellitus (DM) who were using 3-4 injections per day of Insulin and were monitored by continuous glucose monitoring (CGM). The goal was to compare the patient’s glycosylated hemoglobin (HbA1c) taken during their clinic visit by phlebotomy as a marker for diabetic control with estimated HbA1c glucose management indicator (GMI) derived from the 30-day CGM readings. The purpose of the study was to see if there is a correlation between those two values taken within 30- days of each other. To find if there is a correlation is extremely important in assuring that GMI received from the CGM can be used instead of HbA1c in patients on multiple daily injections of Insulin and be incorporated into the American Diabetic Association goals for achieving Diabetes control. Also finding such a correlation can help in reporting the control of diabetes mellitus to other healthcare organizations like Medicare etc. by using CGM data rather than HbA1c. The methodology we used was to compare CGM-derived GMI obtained within 30 – days with HbA1c which has been shown to best correlate with each other. To assess if this difference between GMI and HbA1c was significant, a paired samples t-test was conducted. This comparison is important because of the widespread use of continuous glucose monitoring in patients with Type -1 and Type -2 Diabetes Mellitus on multiple injections of insulin to make treatment decisions. The patients with known factors that can interfere with the accurate measurement of HbA1c like anemia, and liver and kidney diseases were excluded from the study. We concluded the measured HbA1c was 0.34%(4 mmol/mol) higher than the CGM-derived GMI which was the conclusion of several other studies as well. The difference although numerically higher in favor of HbA1c was statistically non-significant. As the use of CGM continues to grow, addressing differences between laboratory-measured HbA1c and CGM-derived GMI is critical. This can affect how we interpret the GMI in patients with CGM compared to HbA1c as well and it can be taken into consideration by different medical organizations while determining the goals of control and reporting of patients with Diabetes mellitus using CGM. Another very important part of the study was that the project was primarily driven by Internal Medicine residents in their clinic and not in a specialized endocrine clinic.